a)x+x+x+x+x=x.5
b)x-3+x-3+x-3+x-3+x-3=x-3.5
A)x+x+x+x+x=-5+(-5)+(-5)+(-5)+(-5)=(-5).5=-25
B)x-3+x-3+x-3+x-3+x-3=-5-3+(-5)-3+(-5)-3+(-5)-3+(-5)-3=(-5)-3.5=-40
a) x+ x+ x+x+x
= x nhân 5
= (-5) x 5
= -25
b) B,x-3+x-3+x-3 +x-3 +x-3
= (x - 3) x 5
= [(-5)-3] x 5
= (-8) x 5 = -40
\(A=x.5=-5.5=-25\)
\(B=\left(x-3\right).5=\left(-5-3\right).5=-8.5=-40\)
Câu B mk cũng không hiểu đề lắm nên hoặc là làm như sau:
\(B=\left(x+x+x+x+x\right)-\left(-3+-3+-3+-3+-3\right)=x.5-\left(-3\right).5=-25-\left(-15\right)=-10\)